2016
DOI: 10.1080/03079457.2016.1142502
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of the Korean H5N8 highly pathogenic avian influenza virus in commercial domestic poultry species

Abstract: In 2014, the highly pathogenic avian influenza (HPAI) virus H5N8 triggered outbreaks in wild birds and poultry farms in South Korea. In the present study, we investigated the pathogenicity of the H5N8 HPAI virus, belonging to the clade 2.3.4.4, in different species of poultry. For this, we examined clinical signs and viral shedding levels following intranasal inoculation of the virus in 3-week-old commercial layer chickens and quails, 10-week-old Korean native chickens, and 8-week-old Muscovy ducks. Intranasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 18 publications
3
36
0
Order By: Relevance
“…Likewise, a range of pathobiological outcomes, from no clinical signs to severe disease including neurological signs, were observed in wild and domestic ducks experimentally inoculated with H5N8 viruses of the same Gs/GD lineage (clade 2.3.4.4), with mortality rates varying from 0 to 20% [1, 29, 58, 59, 6368], and the viruses transmitting efficiently to naïve contacts [6365, 67, 68]. A study describing the pathobiologic characteristics of a H5N1 virus isolated in Canada also belonging to HA clade 2.3.4.4, found that the virus was highly pathogenic to juvenile Muscovy ducks and adult Chinese geese causing systemic infections with neurological signs and mortality (36 and 22% respectively) in both species [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a range of pathobiological outcomes, from no clinical signs to severe disease including neurological signs, were observed in wild and domestic ducks experimentally inoculated with H5N8 viruses of the same Gs/GD lineage (clade 2.3.4.4), with mortality rates varying from 0 to 20% [1, 29, 58, 59, 6368], and the viruses transmitting efficiently to naïve contacts [6365, 67, 68]. A study describing the pathobiologic characteristics of a H5N1 virus isolated in Canada also belonging to HA clade 2.3.4.4, found that the virus was highly pathogenic to juvenile Muscovy ducks and adult Chinese geese causing systemic infections with neurological signs and mortality (36 and 22% respectively) in both species [69].…”
Section: Discussionmentioning
confidence: 99%
“…Naturally or experimentally, mortality in ducks caused by HPAI viruses had been infrequently reported before the Gs/GD H5N1 HPAI outbreaks in Asia [27, 28]. However, many Gs/GD lineage H5N1 HPAI viruses, and recently other Gs/GD-derived H5 viruses, have caused disease and death in domestic ducks (reviewed in [26]) [15, 16, 23, 24, 29]. Similarly, in domestic geese, outcome of infection with H5N1 HPAI viruses depends on the virus strain and the geese species.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high lethality for chickens, its apparent virulence and transmissibility for this species was lower in comparison with A(H5N1) HPAIV (Bertran et al, 2016;Lee et al, 2016a). Despite its high lethality for chickens, its apparent virulence and transmissibility for this species was lower in comparison with A(H5N1) HPAIV (Bertran et al, 2016;Lee et al, 2016a).…”
Section: Human Infections Due To A(h5n6)mentioning
confidence: 95%
“…Since early 2014, HPAI H5N8 has been frequently detected in migratory birds and poultry. 10,11 A single-dose of A/H5N1 influenza vaccine (15 mg) was insufficient to induce a protective immune response. According to the meta-analysis, high-dose ( 30 mg) un-adjuvanted H5N1 influenza vaccine was better immunogenic compare with 15 mg-dose, but the difference was insignificant in case of alum-and non-alum adjuvanted vaccines.…”
Section: Discussionmentioning
confidence: 99%